Narratives of displacement and poverty: the intersections of policy and the shared experience of the everyday - Williams, Lucy (Frontiers in Human Dynamics, 2023)
An extensive, and growing, global literature on the experience of people subject to migration control shows how state actions to ‘manage’ migration and human mobility results in poverty and destitution. There is also a large body of evidence that shows how deeply embedded structures of privilege and inequality lead to the economic deprivation of fully entitled, ‘citizen’ populations. Despite the commonality between these experiences of disadvantage, the impoverishment of migrants and citizens is rarely connected but paying close attention to the stories people with lived experience of poverty tell, challenges the normative assumptions that underpin policy-making on both migration and social inequality. I will argue that listening to, and engaging with, the narratives of people in poverty is an important corrective to the ‘common sense’ that informs much policy making . Focusing on the UK, my aim is to explore the position of people subject to migration control alongside others living in poverty - marginalised and made precarious not by displacement but by deprivation and stigma. Paying close attention to the stories people tell cuts through the official, normative positioning of people as outsiders whether as foreigners or as marginalised citizens. Stories thus reveal the technologies of power and oppression at work in everyday settings that get lost in many analyses. Drawing on concepts including Butler’s ideas of grievability and Mbembe’s necropolitics I will show how the welfare management systems, the hostile environment, for migrants and others living on the margins of society reduces their capacity to act as purposeful human beings. I will reveal the technologies of power and oppression at work in everyday settings and will argue that careful, attentive listening to human stories can challenge the imposition of normative discourses on the voiceless and encourage discourses that embrace complexity.